Fluorinated high-entropy platinum alloy catalyst layer with hydrophobic microenvironment as well as construction method and application of fluorinated high-entropy platinum alloy catalyst layer
By doping fluorine and other non-metallic elements in the high-entropy platinum alloy catalyst, a catalyst layer with a hydrophobic microenvironment is constructed, which solves the activity and stability of the catalyst under operating conditions, and achieves the efficient and high-power density output of the fuel cell.
Patent Information
- Application Number
- CN202411732738.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
It is difficult to achieve high activity and stability under actual operating conditions, and the ORR mass transfer process of the membrane electrode has a large impedance, which affects the performance of the fuel cell.
By doping fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment, it optimizes the electronic structure and strain effect of the catalyst, and improves the diversity of reaction sites and reaction paths.
It has achieved the improvement of the activity and stability of the catalyst at the entire battery level, reduced the mass transfer impedance, enhanced the corrosion resistance, and significantly improved the high-power density performance of the fuel cell.
Smart Images

Figure CN119650730A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical fields of electrochemistry, catalysts and new energy materials, and in particular relates to a fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment and a construction method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFC) have attracted extensive attention and research and development in different fields due to their advantages such as high efficiency, low emissions, fast response speed, low noise, and multiple applicability. Due to the sluggish kinetics of the cathode oxygen reduction reaction (ORR), platinum or platinum-containing alloy catalysts are still needed, but the high price of catalysts has greatly limited the further promotion of PEMFC. Therefore, the fundamental principle of the current development of PEMFC cathode catalysts is to develop catalysts with intrinsic high activity and high stability while further reducing the platinum loading.
[0003] High-entropy platinum alloy catalyst is a new type of catalyst. On the one hand, the structure of the catalyst is stabilized by the combination of multiple metal elements. At the same time, the solid solution effect of each element inhibits the dissolution of transition metals and improves the stability of the catalyst. On the other hand, the platinum loading is reduced by alloying, and the electronic structure and geometric effect of the catalyst surface are changed. At the same time, more reactive sites are provided, the adsorption and conversion of reactants are optimized, and the overall activity of the catalyst is improved. In general, high-entropy platinum alloy catalysts improve the stability of the catalyst and enhance its catalytic activity through the two mechanisms of high entropy effect and alloying.
[0004] Despite the above advantages, the performance of high-entropy platinum alloy catalysts is difficult to express at the membrane electrode level under actual working conditions. Transition metal dissolution, migration, agglomeration, oxidation and other phenomena still occur, and the carbon material carrier is also prone to corrosion. This is mainly due to the complex reaction interface of the full cell, the current density hundreds of times higher than that of the half cell, and the severe working conditions (acidic, humid, and full of oxygen). Therefore, in the design process of the catalyst, it is urgent to consider the construction of the catalyst layer under working conditions, so that a high-activity and high-stability catalyst layer that can operate efficiently in fuel cell devices can be achieved in one step.
[0005] At the full-cell level, in addition to the dissolution, reprecipitation and aggregation of catalyst particles and the coverage of catalyst active sites by ionomers and impurities, which lead to a decrease in ECSA and activity, the ORR mass transfer process of the membrane electrode also plays a key role in the causes of catalyst attenuation. Especially under high currents, the mass transfer impedance of ORR plays a dominant role. Among them, the hydrophilicity (i.e., water management) of the catalyst layer is also a key factor affecting mass transfer. Therefore, the rational design of the cathode catalyst layer so that it has a smaller mass transfer impedance (water removal, proton and oxygen mass transfer), stronger corrosion resistance, etc. while maintaining high activity and stability is still a research focus and difficulty in the field of electrocatalysis and requires further exploration. Summary of the invention
[0006] The purpose of the present invention is to provide a fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment and a construction method and application thereof. Doping with other non-metallic elements (N, B) other than fluorine can not only adjust the hydrophilicity and hydrophobicity of the catalyst layer, but also through the synergistic effect of fluorine and other non-metallic elements, while maintaining the inherent advantages of high entropy platinum alloys, it can further optimize the electronic structure and strain effect of the catalyst, provide more reaction sites and reaction paths, thereby further improving the activity and stability of the catalyst. In addition, the surface properties (hydrophilicity and hydrophobicity, mechanical, and mass transfer aspects) of the fluorinated high entropy platinum alloy catalyst layer are further optimized by the synergistic effect of these non-metallic (N, B), so that the activity and stability of the constructed catalyst layer at the full cell level are further improved, especially in achieving a qualitative breakthrough in achieving high power density of fuel cells.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The present invention provides a fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment, comprising:
[0009] Fluorinated high entropy platinum alloy catalyst;
[0010] A catalyst layer consisting of a fluorine-doped carbon support and a Nafion ionomer solution; wherein:
[0011] The hydrophobicity of the catalyst layer can be further regulated by doping other light non-metallic elements (N, B) in the particles of the fluorinated high entropy platinum alloy catalyst and the fluorinated carbon support.
[0012] Furthermore, the fluorinated high entropy platinum alloy catalyst in the catalyst layer includes at least PtCuNiCoF, PtCuNiCrF, PtCuNiFeF, PtCuNiCoNF, and PtCuNiCoNBF.
[0013] Furthermore, the mass ratio of the Nafion ionomer solution is 4%-7%, and the mass ratio of the Nafion ionomer solution to the carbon carrier is 0.45-0.8.
[0014] A method for constructing a fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment is characterized in that it comprises the following steps: dissolving a certain amount of fluorinated high-entropy platinum alloy catalyst, a fluorinated carbon carrier and a Nafion ionomer in a mixed solvent of isopropanol and H2O; ultrasonicating under water bath conditions to obtain a cathode catalyst ink; and spraying the uniform catalyst ink at a certain rate on one side of a proton exchange membrane by an ultrasonic sprayer to form a fluorinated high-entropy platinum alloy catalyst layer.
[0015] Furthermore, the preparation method of the fluorinated high entropy platinum alloy catalyst comprises the following steps:
[0016] Step 1, after uniformly dispersing the platinum precursor, 3d transition metal precursor, structure directing agent, fluorine source or continuing to add other N, B non-metallic sources and solvent by ultrasonic dispersion, the carbon carrier is added and ultrasonic dispersion is continued to obtain a mixture;
[0017] Step 2: The mixture is heated in an oil bath while being stirred, and after the reaction is completed, it is cooled to room temperature.
[0018] Centrifugal washing and vacuum drying are performed to obtain the initial catalyst;
[0019] Step 3, annealing the initial catalyst in a reducing atmosphere, and then cooling it to room temperature to obtain a stable catalyst;
[0020] Step 4: centrifugally wash and dry the above-mentioned stable catalyst, and after acid treatment under an inert atmosphere, repeat the previous centrifugation washing and drying steps to obtain the final fluorinated high entropy platinum alloy catalyst.
[0021] Furthermore, in step 1:
[0022] The platinum precursor is one of acetylacetonate platinum, hexahydrate chloroplatinic acid, sodium chloroplatinate, and potassium chloroplatinate;
[0023] The transition metal precursor is at least one of chloride, chlorate, nitrate, acetate and acetylacetonate of transition metal;
[0024] The fluorine source is any one of perfluorobenzene, tetrafluoroterephthalic acid, PTFE, tetrafluoroterephthalonitrile, 2-fluoropyridine, ammonium fluoride, hexafluorobenzene, and PVDF;
[0025] The nitrogen source is any one of ammonia water, ammonium nitrate, ammonium bicarbonate, ammonium chloride, urea, melamine, pipemidic acid, and 1,3-diamidazole; the boron source is any one of boric acid, phenylboric acid, sodium tetraborate, sodium borohydride, boric acid alcohol, and dimethylamine borane;
[0026] The structure directing agent is any one of phenylacetic acid, benzoic acid, o-toluic acid and acetic acid.
[0027] The directing agent also plays a certain reducing role;
[0028] The solvent is any one of dimethylamide, tetrahydrofuran and dimethyl sulfoxide, and the solvent also plays a reducing role.
[0029] The molar ratio of the platinum precursor to each transition metal precursor, the reducing agent, the non-metal source and the carbon black is 0.5-1.5:1:40-55:8-11:30-40.
[0030] Furthermore, in step 2:
[0031] The reaction temperature is 160°C, the heating rate is 1-3°C / min, and the holding time is 8-16h;
[0032] The solvent used for washing the mixture is at least one of deionized water, ethanol, acetone and cyclohexane, and the drying temperature is 40-100°C.
[0033] Furthermore, in step three:
[0034] The annealing atmosphere is one of 10% H2 / Ar or N2, and the annealing temperature is 300-500°C;
[0035] In step 4:
[0036] The inert atmosphere is one of Ar or N2, the acid solution is one of nitric acid or sulfuric acid, the molar concentration is 0.1-1 mol / L, the acid treatment time is 8-10h, and the acid treatment temperature is 60-100°C.
[0037] Furthermore, the spraying temperature is 55-65°C and the spraying distance is 9-11 cm2.
[0038] Furthermore, the initial catalyst has the characteristics of a fluorinated high entropy platinum alloy catalyst after a one-step solvent thermal reaction.
[0039] Furthermore, the final catalyst comprises fluorinated high entropy platinum alloy particles and fluorinated carbon carriers.
[0040] Furthermore, the particles of the final catalyst may also contain sites co-doped with other non-metallic elements (N, B).
[0041] Furthermore, the carbon carrier of the final catalyst contains metal unit atomic sites and may also contain heteroatom sites co-doped with other non-metallic elements (N, B).
[0042] Furthermore, the nanoparticle size of the fluorinated high entropy platinum alloy catalyst particles with a hydrophobic microenvironment is 2-8 nm.
[0043] Furthermore, the construction of the fluorinated high entropy platinum alloy catalyst layer includes:
[0044] A certain amount of fluorinated high entropy platinum alloy catalyst, fluorinated carbon carrier and Nafion ionomer were dissolved in a mixed solvent of 75wt% isopropanol and 25wt% H2O, and ultrasonicated for 40mins under water bath conditions to obtain cathode catalyst ink; the uniform catalyst ink was sprayed on one side of the proton exchange membrane at a rate of 0.2ML / min by an ultrasonic sprayer to form an active area of 5cm 2 of a fluorinated high entropy platinum alloy catalyst layer.
[0045] The present invention also provides an application of a fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment in the operation of a fuel cell, which can significantly improve the performance in water management, oxygen mass transfer, activity and stability.
[0046] The present invention also provides an application of a fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment in an oxygen reduction reaction (ORR) at a cathode of a fuel cell.
[0047] Compared with the prior art, the beneficial technical effects of the present invention are:
[0048] (1) The method for constructing a fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment provided by the present invention is to construct a perfluorinated hydrophobic microenvironment by fluorination of catalyst particles and carriers and NAFION ionomer solution. The doping of fluorine elements in catalyst particles can not only achieve the purpose of reducing the platinum loading, but also can further improve the activity and stability of the catalyst by continuously regulating the electronic structure and geometric structure of the high entropy platinum alloy. In addition, the doping of F with the strongest electronegativity in particles and substrates can effectively reduce the electron density (CF or MF bonds) of the surrounding environment, thereby improving the antioxidant capacity of catalyst particles and carbon carriers, and greatly improving the stability of the material, which is more obvious in a highly corrosive full-battery environment. Moreover, the formation of CF bonds on the catalyst carrier changes the electronic distribution and polarity of the surface of the carbon material, so that the free energy of the surface of the carbon material is reduced, and the surface presents a non-polar state, so that the hydrogen bonding effect with water becomes weak, that is, the hydrophobicity is strong. By designing a fully fluorinated catalyst layer, we can reduce the mass transfer impedance of the fuel cell while ensuring smooth proton transmission, which is beneficial to the removal of water vapor and effectively improves the stability of the material at the full cell level.
[0049] (2) In addition, since the electronegativity and polar hydrophobicity of the three elements B, N, and F gradually increase. By doping with other non-metallic elements (N, B) except fluorine, the hydrophilicity and hydrophobicity of the catalyst layer can be regulated, and the optimization of the surface characteristics of the catalyst layer brought about by the doping of different elements can also be taken into account. For example, the doping of B atoms is beneficial to improving the mechanical strength and structural stability of the high-entropy catalyst particles, while regulating the electron density on the catalyst surface, which is beneficial to the reaction rate of specific elementary reactions in the ORR reaction. The doping of N optimizes the electronic structure and geometric structure of the catalyst, which is beneficial to improving the activity and stability of the catalyst. The simultaneous doping of fluorine and other elements (N, B) can optimize the surface characteristics of the catalyst layer. This synergistic effect has a certain regulatory effect on the mechanical strength, hydrophobicity, mass transfer, activity and stability of the catalyst layer, and its effect is far better than the catalyst layer constructed by a single non-metallic doped high-entropy alloy catalyst.
[0050] (3) The fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment constructed by the present invention has excellent electrochemical performance in fuel cells, especially in terms of improving high power density performance. The catalyst layer constructed by the fluorinated high entropy alloy PtCuNiCo-NF / C-NF co-doped with nitrogen has a mass activity (MA) of 4.2 A / mg at the half-cell level (0.9 V (vs. RHE) Pt The mass activity MA is also in a leading position in the currently reported literature and patents. In addition, the outstanding mass activity of the catalyst can be well expressed at the membrane electrode level. Pt cm -2 The catalyst is applied to the cathode of H2-Air fuel cells, and the peak power density can reach 1.31 Wcm -2 , and the rated power at 0.65V is 1.16Wcm -2 Its excellent performance in H2-Air fuel cell PEMFC and the ultra-high power density it can express are at the top level in the industry. In summary, the hydrophobic microenvironment constructed by the patent of this invention and the fluorinated high-entropy platinum alloy catalyst layer doped with nitrogen are not only highly active and stable, but also the performance indicators expressed at the level of single-section membrane electrode have far exceeded all the core indicators of the US Department of Energy (DOE) in 2025 (total platinum loading <0.125mg Pt cm -2 , at 0.9V, mass activity> 0.44A / mg Pt ). BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The present invention will be further described below in conjunction with the accompanying drawings.
[0052] Figure 1is a low-resolution TEM image of the fluorinated high-entropy platinum alloy PtCuNiCoF-1 / CF catalyst after activation in Example 1 of the present invention;
[0053] Figure 2 This is a statistical diagram of the particle size distribution of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst in Example 1 of the present invention.
[0054] Figure 3 HAADFSTEM and corresponding EDS elemental analysis images of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst in Example 1 of the present invention.
[0055] Figure 4 This is the XRD spectrum of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst in Example 1 of the present invention.
[0056] Figure 5 The LSV curve of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst and TKK20% Pt / C in the half-cell in Example 1 of the present invention ( Figure 5 a) and decay diagram of mass activity and intrinsic activity after accelerated cycling (AST) test ( Figure 5 b).
[0057] Figure 6 Polarization curves and power density diagrams of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst layer constructed in Example 1 of the present invention in the H2-AIR fuel cell in the initial state and after 30,000 cycles of AST testing.
[0058] Figure 7 This is a comparison diagram of the LSV curves of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF in Example 1 of the present invention and the PtCuNiCo / C catalyst in Example 2.
[0059] Figure 8 This is an LSV curve diagram of the catalysts PtCuNiCoF-1 / CF, PtCuNiCoF-2 / CF and TKK20%Pt / C with different fluorine doping in Example 1 of the present invention under half-cell test.
[0060] Fig. 9 The LSV curve of the catalyst synthesized by other transition metal elements in the fourth period is obtained by extending the preparation method of the fluorinated high entropy platinum alloy with a hydrophobic microenvironment in Example 1 of the present invention.
[0061] Fig.10These are low-resolution TEM images of the fluorinated high-entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF after activation, which are regulated by non-metallic elements (N, B) and have a hydrophobic microenvironment in Examples 5 and 6 of the present invention.
[0062] Fig.11 Statistical graphs of particle size distribution of fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF with a hydrophobic microenvironment regulated by non-metallic elements (N, B) in Examples 5 and 6 of the present invention.
[0063] Fig.12 HAADF-STEM and corresponding EDS elemental analysis images of the fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF with a hydrophobic microenvironment regulated by non-metallic elements (N, B) in Examples 5 and 6 of the present invention.
[0064] Fig.13 XRD patterns of the fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF with a hydrophobic microenvironment regulated by non-metallic elements (N, B) in Examples 5 and 6 of the present invention.
[0065] Fig.14 LSV curves of the fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF, PtCuNiCo-BNF / C-BNF with a hydrophobic microenvironment regulated by non-metallic elements (N, B) in Examples 5 and 6 of the present invention, as well as commercial TKK20% Pt / C in half cells.
[0066] Fig.15 Polarization curves and power density diagrams of the fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF, PtCuNiCo-BNF / C-BNF with a hydrophobic microenvironment regulated by non-metallic elements (N, B) in Examples 5 and 6 of the present invention and commercial TKK20% Pt / C in H2-AIR.
[0067] Fig.16 Polarization curves and power density diagrams of the nitrogen-doped fluorinated high-entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer constructed in Example 5 of the present invention in the H2-AIR fuel cell in the initial state and after 30,000 cycles of AST testing.
[0068] Fig.17 This is the XRD spectrum of the catalyst prepared in Comparative Example 2 without adding Pt precursor.
[0069] Fig.18 This is the TEM and particle size distribution diagram of the initial catalyst after the solvothermal reaction in step 2 of comparative example 2 is completed.
[0070] Fig.19 This is a comparison chart of the electrochemical performance of the catalyst prepared in Comparative Example 2 without high-temperature heat treatment in step 3 and with high-temperature heat treatment.
[0071] Fig. 20 These are experimental contact angle graphs of the fluorinated high entropy platinum alloy catalyst PtCuNiCoF-1 / CF in Example 1, the PtCuNiCo / C catalyst in Example 2, and the fluorinated high entropy platinum alloy catalyst PtCuNiCo-NF / C-NF with a hydrophobic microenvironment regulated by nitrogen doping in Example 5.
[0072] Fig.21 These are the corresponding polarization separation diagrams of the fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF and PtCuNiCo-F / CF catalyst layers with a hydrophobic microenvironment constructed in Examples 5 and 6 of the present invention under H2-AIR conditions. DETAILED DESCRIPTION
[0077] The specific information of the raw materials used in the examples and comparative examples of the present invention are as follows:
[0078] Metal precursor materials: platinum acetylacetonate (97%), copper acetylacetonate (97%), nickel acetylacetonate (95%), cobalt acetylacetonate (97%), iron acetylacetonate (98%), chromium acetylacetonate (98%), manganese acetylacetonate (97%); all from McLean manufacturers.
[0079] Structure directing agent: benzoic acid (99%, McLean) Non-metal source: tetrafluoroterephthalonitrile (98%, Aladdin) Piperidinic acid (98%, Aladdin), 2-fluoropyridine (99%, Aladdin), phenylboronic acid (97%, McLean).
[0080] Carbon material: Ketjen black (ECP-600JD, Kelude).
[0081] Solvent: dimethylformamide (99.5%, Aladdin), acetone (analytical grade 500 mL, Sinopharm Shanghai test), ethanol (99.7%, Sinopharm Shanghai formula).
[0082] Materials used for electrochemical testing in the embodiments of the present invention: deionized water (18.2 MΩ*cm@25°C), nitric acid (68%, Sinopharm Shanghai formula), Nafion solution (D5205% 10 mL, Suzhou Shengernuo Technology Co., Ltd.), and anhydrous ethanol (analytical grade 500 mL, Sinopharm Shanghai test).
[0083] The present invention provides a method for constructing a fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment, the main steps of which are:
[0084] (1) Preparation of Fluorinated Carbon-Supported High Entropy Platinum Alloy Catalyst
[0085] Step 1: After uniformly dispersing the platinum precursor, 3d transition metal precursor, reducing agent, fluorine source (or continuing to add other N, B non-metallic sources) and solvent by ultrasonic dispersion, the carbon carrier is added and ultrasonic dispersion is continued to obtain
[0086] to a mixture; wherein the molar ratio of the platinum precursor to each transition metal precursor, the reducing agent, the non-metallic source, and the carbon black is 0.5-1.5:1:40-55:8-11:30-40.
[0087] Step 2: The mixture is stirred in an oil bath while being heated to 160°C at a heating rate of 1-3°C / min and maintained for 8-16 hours. After the reaction is completed, the mixture is cooled to room temperature and washed with deionized water,
[0088] Wash by centrifugation with ethanol and acetone for 3-5 times and dry under vacuum at 40-100°C to obtain an initial catalyst;
[0089] Step 3, annealing the initial catalyst at 300-500° C. for 3-6 hours in a 10% H2 / Ar atmosphere, and then cooling to room temperature to obtain a stable catalyst;
[0090] Step 4: centrifugally wash and dry the above-mentioned stable catalyst with deionized water, ethanol and acetone, and then treat it with 0.1-1 mol / L nitric acid at 60-100° C. for 8-10 hours under Ar atmosphere, and then repeat the centrifugal washing and drying steps of step 2 to obtain the final fluorinated high entropy platinum alloy catalyst.
[0091] (2) Construction of a fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment
[0092] A certain amount of fluorinated high entropy platinum alloy catalyst, fluorinated carbon carrier and Nafion ionomer were dissolved in a mixed solvent of 75wt% isopropanol and 25wt% H2O, wherein the mass ratio of Nafion ionomer solution was 4%-7%, and the mass ratio of Nafion ionomer to carbon carrier was 0.45-0.8; ultrasonic treatment was performed for 40mins under water bath conditions.
[0093] obtaining cathode catalyst ink;
[0094] The catalyst ink was uniformly sprayed on one side of the proton exchange membrane at a rate of 0.2 ML / min by an ultrasonic sprayer at a temperature of 55-65°C and a spraying distance of 9-11 cm2, forming an active area of 5 cm 2 fluorinated high entropy platinum alloy catalyst layer.
[0095] The present invention provides a method for constructing a fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment. The catalyst layer is applied to the cathode oxygen reduction reaction of a fuel cell, showing excellent electrochemical performance. It not only has ultra-high catalyst activity and stability, but also achieves high power density output in the fuel cell device under working conditions. This performance improvement is at the top level in the industry.
[0096] Example 1
[0097] This embodiment 1 provides a method for constructing a fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst layer having a hydrophobic microenvironment, comprising:
[0098] (1) Preparation of fluorinated carbon-supported high entropy platinum alloy catalyst PtCuNiCoF-1 / CF
[0099] Step 1, dissolving 10 mg of platinum acetylacetonate, 6.7 mg of copper acetylacetonate, 6.5 mg of nickel acetylacetonate, 6.5 mg of cobalt acetylacetonate, 150 mg of benzoic acid, and 50 mg of tetrafluoroterephthalonitrile in dimethylformamide, and then further ultrasonically dispersing 10 mg of carbon black therein to obtain a mixture;
[0100] Step 2: Stir the mixture in an oil bath while heating it to 160°C at a rate of 5°C / mins and maintaining it for 12 hours. After the reaction is completed, cool it to room temperature, wash it by centrifugation for 3-5 times with a mixed liquid of deionized water, ethanol and acetone, and dry it in vacuum at 60°C to obtain an initial fluorinated carbon-supported platinum alloy carbon-supported catalyst PtCuNiCoF-1 / CF.
[0101] Step three, annealing the above product at 400° C. for 4 h under 10% H2 / Ar, and then cooling to room temperature to obtain a stable fluorinated carbon-supported platinum alloy carbon-supported catalyst PtCuNiCoF-1 / CF.
[0102] Step 4: The above-mentioned stable catalyst is centrifugally washed 3-5 times with a mixed liquid of deionized water, ethanol and acetone, and then pickled with 0.2 mol / L nitric acid solution at 80°C for 8h, and then the washing and drying steps in step 2 are repeated to obtain the final PtCuNiCoF-1 / CF.
[0103] (2) Construction of a fluorinated high-entropy platinum alloy PtCuNiCoF-1 / CF catalyst layer with a hydrophobic microenvironment
[0104] 20 mg of fluorinated high entropy platinum alloy catalyst, fluorinated carbon carrier and Nafion ionomer were dissolved in a mixed solvent of 75 wt % isopropanol and 25 wt % H2O, wherein the mass ratio of Nafion ionomer solution was 5%, and the mass ratio of Nafion ionomer solution to carbon carrier was 0.8; ultrasonication was performed for 40 mins under water bath conditions to obtain cathode catalyst ink;
[0105] The uniform catalyst ink was sprayed on one side of the proton exchange membrane at a rate of 0.2ML / min using an ultrasonic sprayer at a temperature of 60°C and a spraying distance of 10cm2 to form a fluorinated high-entropy platinum alloy catalyst layer PtCuNiCoF-1 / CF with an active area of 5cm2.
[0106] Figure 1 is a low-resolution TEM image of the fluorinated high-entropy platinum alloy PtCuNiCoF-1 / CF catalyst after activation in Example 1 of the present invention; Figure 2 : is a statistical diagram of the particle size distribution of the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst in Example 1 of the present invention. Figure 1 and Figure 2 As shown, the PtCuNiCoF-1 / CF catalyst particles prepared in Example 1 are uniformly dispersed on the porous carbon, and the average particle size is about 5.7 nm. Figure 3 This is the HAADF-STEM and corresponding EDS elemental analysis image of the PtCuNiCoF-1 / CF catalyst. It can be seen from the figure that Pt, Cu, Ni, Co, and F are all present, and the F element is not only evenly dispersed in the particles, but also exists on the carbon substrate. Figure 4 The XRD spectrum of the PtCuNiCoF-1 / CF catalyst. As can be seen from the figure, similar to Pt / C, PtCuNiCoF-1 / CF also forms a single-phase FCC structure dominated by the (111) crystal plane, and no other 3D-transition metal phase segregation is found. In addition, the diffraction peaks of PtCuNiCoF-1 / CF shift to higher angles, indicating that due to the doping of transition metal elements with smaller atomic diameters, the corresponding crystal plane spacing of these platinum alloys has shrunk to a certain extent.
[0107] In order to verify the electrochemical activity of the hydrophobic fluorinated high entropy platinum complex PtCuNiCoF-1 / CF catalyst layer constructed in Example 1 in a fuel cell, we tested its electrochemical performance in a half-cell and a full-cell. First, we conducted an electrochemical test in a rotating disk electrode, and the specific steps are as follows:
[0108] 20 mg of the PtCuNiCoF-1 / CF catalyst prepared in Example 1 was mixed with 990 μL of anhydrous ethanol and 10 μL of Nafion solution, and the mixture was ultrasonically treated for 1 h to obtain a uniformly mixed black ink.
[0109] The catalyst ink was drawn with a pipette and coated on a glassy carbon (GC) electrode with a diameter of 5 mm. This electrode was used as a working electrode, and a three-electrode test system was formed with a platinum wire electrode as a counter electrode, an Ag / AgCl electrode as a reference electrode, and a 0.1 M perchloric acid solution as an electrolyte. The catalyst was tested under this system, oxygen was continuously introduced, and cyclic voltammetry (CV) scanning was performed to activate the catalyst while maintaining sufficient dissolved oxygen in the electrolyte. The scanning range was -0.05V-0.95V and the scanning speed was 200mVs -1 , the number of scan cycles is 60; after activation, a linear sweep voltammetry (LSV) test is performed with a scan range of -0.05V-1.1V and a scan rate of 10mVs -1 , and obtain the polarization curve of the catalyst.
[0110] The specific steps of the accelerated durability test (ADT) of the PtCuNiCoF-1 / CF catalyst are as follows: 20,000 cycles of CV scanning were performed with a scanning range of 0.4 V to 0.9 V (relative to the reversible hydrogen electrode) and a scanning speed of 200 mVs -1 .
[0111] Figure 5 The LSV curves of PtCuNiCoF-1 / CF and commercial TKK20%Pt / C catalysts under half-cell and the columnar attenuation graph of mass activity and intrinsic activity after accelerated cycle test (AST). It can be seen from the figure that after 20,000 cycles, the mass activity and intrinsic activity of PtCuNiCoF-1 / CF lost 23.4% and 15% respectively, while the mass activity and intrinsic activity of commercial TKK20%Pt / C decayed by 42.2% and 35.8% respectively after 20,000 cycles.
[0112] Next, we use the constructed PtCuNiCoF-1 / CF catalyst layer to continue preparing the membrane electrode. The specific steps are as follows:
[0113] The anode catalyst layer was obtained by coating TKK20% Pt / C on the other side of the PEM in the same construction method as the cathode catalyst layer;
[0114] The PEM containing the cathode and anode catalyst layers, two gas diffusion layers (GDL) and two polyimide membrane gaskets are pressed together by a hot press to form a membrane electrode (MEA). The hot press conditions are: 120°C, 4MPa, 5min.
[0115] The electrochemical test conditions were: cell temperature 80°C, 100% RH, 1.5 bar back pressure, H2 and air flow rates of 0.2 and 1.0 L min, respectively. -1 .
[0116] Figure 6 The PtCuNiCoF-1 / CF membrane electrode and its polarization curve and peak power density after 30,000 cycles of AST test are shown. As can be seen from the figure, the total loading of the anode and cathode is 0.1 mg. Pt cm -2 In the case of PtCuNiCoF-1 / CF film electrode, the initial peak power density is 1.01 W / cm 2 After 30,000 cycles of AST testing, the peak power density of PtCuNiCoF-1 / C is 0.68W / cm 2 , reduced by 34%. This shows that the fluorinated high entropy platinum alloy PtCuNiCoF-1 / CF catalyst layer with a hydrophobic microenvironment constructed by the present invention has good stability in the full battery.
[0117] Example 2
[0118] This embodiment is a variation of embodiment 1, the variation being that the fluorine source in the present invention is removed, and the other conditions are the same as those in embodiment 1.
[0119] In order to verify the effect of fluorine doping on the performance of the catalyst fuel cell, the PtCuNiCoF-1 / CF of Example 1 and the PtCuNiCo / C catalyst prepared in this example were subjected to half-cell performance tests. Figure 7 From the LSV curves, it can be seen that the catalytic activities of PtCuNiCo / C and PtCuNiCoF-1 / CF are gradually improved. Their half-wave potentials are 0.943V and 0.957V, respectively, and the mass activities calculated at 0.9V (relative to RHE) are 1.26Amg pt -1 and 2.56Amg pt -1 This indicates that the performance of the fluorinated high-entropy platinum alloy PtCuNiCoF-1 / CF catalyst with a hydrophobic microenvironment is better than that of the high-entropy platinum alloy without fluorine doping.
[0120] Example 3
[0121] This embodiment aims to regulate the influence of the content of doped fluorine element on the electrochemical performance of the constructed fluorinated high entropy platinum alloy catalyst layer in a fuel cell.
[0122] The fluorinated high entropy platinum alloy catalyst PtCuNiCoF / CF with a hydrophobic microenvironment in this embodiment was prepared by the same steps as in Example 1, except that:
[0123] In step 1, the amount of fluorine source, i.e., tetrafluoroterephthalonitrile, added was controlled to be 10 mg, 50 mg, 100 mg, and 150 mg, respectively, and the other conditions were the same as those in Example 1.
[0124] From Table 1, we can see that the final F doping amounts are 2.7%, 2.2%, 4.5% and 3% respectively. We selected two samples PtCuNiCoF-1 / CF and PtCuNiCoF-2 / CF with final F doping amounts of 2.2% and 4.5% for half-cell electrochemical testing and compared them with commercial TKK20% Pt / C. Figure 8 From the LSV curves shown, it can be seen that the ORR activity of TKK20% Pt / C, PtCuNiCoF-2 / CF and PtCuNiCoF-1 / CF gradually increases, among which PtCuNiCoF-1 / CF has the best ORR activity. The half-wave potentials of these three catalysts are 0.90V, 0.93V, and 0.957V, respectively, showing a gradual increase. The mass activity calculated at 0.9V (relative to RHE) shows the same trend, and the mass activity of PtCuNiCoF-1 / CF (2.56Amg pt -1 ) are PtCuNiCoF-2 / CF(1.8Amg pt -1 ) and TKK20% PtCo (0.45Amg pt -1 The above results show that the final doping amount of F is not as high as possible, and when the doping amount of F is 2.2%, the improvement of activity is more obvious.
[0125] Table 1 F doping amount corresponding to the fluorinated high entropy platinum alloy catalyst prepared by different fluorine source input amounts in Example 1
[0126] Fluoride source input (mg) F doping amount in the product (atomic percentage) 10 2.7 50 2.2 100 4.5 150 3
[0127] Example 4
[0128] This embodiment is a variation of Embodiment 1, and the variation is that the transition metal elements of the transition metal precursor in the present invention are expanded to most of the transition metal elements in the fourth period, and the other conditions are the same as those in Embodiment 1.
[0129] Fig. 9The LSV curves of catalysts synthesized by extending the preparation method in Example 1 of the present invention to other transition metal elements of the fourth period. Table 1 summarizes the half-wave potentials of these catalysts and the corresponding MA at 0.9 V (relative to RHE).
[0130] from Fig. 9 It can be seen that the preparation method of the fluorinated high entropy platinum alloy catalyst with a hydrophobic microenvironment provided by the present invention can be extended to most of the transition metals in the fourth period through different transition metal precursors. From Table 2, it can be seen that the half-wave potential, mass and intrinsic activity of the fluorinated high entropy platinum alloy catalyst containing Pt, Cu, and Ni metal elements are higher than those of platinum alloy catalysts of other element combinations, and the catalytic activity is also better. It is foreseeable that the catalyst layer constructed by these fluorinated high entropy platinum alloys has good application prospects in actual fuel cells.
[0131] Table 2 LSV curves of a series of fluorinated high entropy platinum alloy catalysts prepared in Example 4 ( Fig. 9 ) and the values of mass activity (MA) and intrinsic activity (SA) calculated at 0.9 V.
[0132]
[0133] Example 5
[0134] In order to further control the surface properties of the constructed fluorinated high entropy platinum alloy catalyst layer (such as hydrophilicity, activity and stability, etc.), we achieve this by doping other non-metallic elements (N, B). This embodiment provides a method for constructing a fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer with a hydrophobic microenvironment, including:
[0135] (1) Preparation of Fluorinated Carbon-supported High Entropy Platinum Alloy Catalyst PtCuNiCo-NF / C-NF
[0136] Step 1, dissolving 10 mg of platinum acetylacetonate, 6.7 mg of copper acetylacetonate, 6.5 mg of nickel acetylacetonate, 6.5 mg of cobalt acetylacetonate, 150 mg of benzoic acid, 38 mg of pipemidic acid, and 12.1 mg of 2-fluoropyridine in dimethylformamide, and then ultrasonically dispersing 10 mg of carbon black therein to obtain a mixture;
[0137] Step 2, stirring the mixture in an oil bath while heating it to 160° C. at a rate of 5° C. / mins and maintaining it for 12 hours. After the reaction is completed, the mixture is cooled to room temperature, centrifuged and washed, and vacuum dried at 60° C. to obtain an initial PtCuNiCo-NF / C-NF catalyst;
[0138] Step 3, annealing the above product at 400° C. for 4 h under 10% H2 / Ar, and then cooling to room temperature to obtain a stable PtCuNiCo-NF / C-NF catalyst;
[0139] Step 4: The above-mentioned stable catalyst is centrifugally washed 3-5 times with a mixed liquid of deionized water, ethanol and acetone, then pickled with 0.2 mol / L nitric acid solution at 80°C for 8h, and then the washing and drying steps in step 2 are repeated to obtain the final PtCuNiCo-NF / C-NF.
[0140] (2) Construction of a fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer with a hydrophobic microenvironment: 20 mg of fluorinated high entropy platinum alloy catalyst, fluorinated carbon support and Nafion ionomer were dissolved in a mixed solvent of 75 wt % isopropanol and 25 wt % H2O, wherein the mass ratio of the Nafion ionomer solution was 5%, and the mass ratio of the Nafion ionomer solution to the carbon support was 0.8; ultrasonication was performed for 40 mins under water bath conditions to obtain cathode catalyst ink; and the coating was performed by ultrasonic spraying at a temperature of 60 ° C and a spraying distance of 10 cm. 2 The uniform catalyst ink was sprayed on one side of the proton exchange membrane at a rate of 0.2 ML / min to form a fluorinated high entropy platinum alloy catalyst layer PtCuNiCo-NF / C-NF with an active area of 5 cm2.
[0141] Example 6
[0142] This embodiment provides a method for constructing a fluorinated high entropy platinum alloy PtCuNiCo-BNF / C-BNF catalyst layer with a hydrophobic microenvironment. The catalyst layer is constructed using the same steps as in Example 3, except that the non-metal source is changed from 38 mg of pipemidic acid and 12.1 mg of 2-fluoropyridine in Example 3 to 10 mg of phenylboronic acid, 25 mg of pipemidic acid, and 8.1 mg of 2-fluoropyridine, and the remaining steps are the same as in Example 3.
[0143] Example 7
[0144] This example uses XRD, TEM, and EDS MAPPING to verify whether the N, B-doped fluorinated high-entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF prepared in Examples 5-6 are successful.
[0145] Fig.10 These are low-resolution TEM images of the PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / CBNF catalysts prepared in Examples 5-6 of the present invention after activation. Fig.11 The particle size distribution statistics of the fluorinated high entropy platinum alloy catalyst prepared in Embodiment 5-6 of the present invention are shown in FIG. Fig.10 and Fig.11 As shown, the PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF catalyst particles prepared in Examples 5-6 are uniformly dispersed on the porous carbon, and their average particle sizes are 3.85 and 3.88 nm, respectively. Fig.12 The HAADF-STEM and corresponding EDS elemental analysis images of the catalysts synthesized in Examples 5-6 of the present invention show that, according to the components of the synthesized catalysts, Pt and transition metal elements and non-metallic elements are present in the particles, forming heteroatom sites doped with non-metallic elements and single atom sites of transition metals on the carbon substrate. Fig.13 The XRD patterns of the above catalysts are shown in Figure 2. Compared with Pt / C, the diffraction peaks of PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF catalysts are shifted to higher angles, indicating that due to the doping of transition metal elements with smaller atomic diameters, the corresponding interplanar spacing of these platinum alloys has shrunk to a certain extent. The above results prove that we have successfully synthesized fluorinated high-entropy platinum alloy catalysts doped with non-metallic elements (B, N).
[0146] Example 8
[0147] In order to verify the electrochemical activity of the fluorinated high-entropy platinum alloy PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF catalyst layers constructed in Examples 5 and 6 in fuel cells, we tested their electrochemical performance in half cells and full cells, respectively.
[0148] Fig.14 It is the LSV curve of the fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF doped with non-metallic elements (N, B) synthesized in Examples 5-6. As can be seen from the figure, the activity of these two non-metallic element doped catalysts is much higher than that of commercial Pt / C catalysts, among which the ORR activity of PtCuNiCo-BNF / C-BNF and PtCuNiCo-NF / C-NF is gradually improved. Their half-wave potentials are 0.89, 0.96, and 0.98V, respectively, showing a trend of gradual increase. The mass activity calculated at 0.9V (relative to RHE) shows the same trend, which are 0.3, 2.7, and 4.2Amgpt-1, respectively, which is much higher than the mass activity of TKK20% Pt / C catalyst.
[0149] Fig.15The polarization curves and power density diagrams of the non-metallic element (N, B) doped fluorinated high entropy platinum alloy catalysts PtCuNiCo-NF / C-NF and PtCuNiCo-BNF / C-BNF in H2-AIR are shown in the figure. Pt / cm 2 , cathode loading is 0.1 mg Pt / cm 2 In the case of PtCuNiCo-NF / C-NF, PtCuNiCo-BNF / C-BNF, and commercial TKK20% Pt / C membrane electrode, the peak power density is 1.31 W / cm 2 , 1.25W / cm 2 、0.95W / cm 2 This shows that the performance of PtCuNiCo-NF / C-NF membrane electrode is better than that of PtCuNiCo-BNF / C-BNF catalyst and much higher than that of commercial TKK20% Pt / C membrane electrode.
[0150] Fig.16 The polarization curve and peak power density diagram of the non-metal (N, B) doped fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer with a hydrophobic microenvironment constructed in Example 5 before and after 30,000 AST cycles in a H2-AIR fuel cell. It can be seen from the figure that when the anode loading is fixed at 0.025 mg Pt / cm 2 , cathode loading is 0.1 mg Pt / cm 2 In the case of AST test, after 30,000 cycles, the peak power density and rated power of PtCuNiCoNF / C-NF at 0.67V were 1.125W / cm 2 、0.92W / cm 2 , compared with the initial peak power density (1.35W / cm 2 ) and rated power (1.16W / cm 2 ), the retention rates reached 83% and 79% respectively. Compared with the commercial platinum carbon published in Nature Catalysis by Peng B.S et al. in 2024, after 30,000 cycles of AST test, the rated power retention rate at 0.67V was only 37%. The above results show that the non-metal (N, B) doped fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer with a hydrophobic microenvironment constructed in the present invention has very excellent stability in H2-AIR, far exceeding commercial Pt / C.
[0151] Comparative Example 1
[0152] This comparative example demonstrates that the activity of the fluorinated high-entropy platinum alloy catalyst doped with non-metallic elements is superior to that of the single fluorine-doped high-entropy platinum alloy catalyst by comparing the electrochemical properties of PtCuNiCoF-1 / CF in Implementation 1 with the PtCuNiCo-NF / C-NF in Example 5.
[0153] Table 3 shows the results of these catalysts at a cathode loading of 0.1 mg Pt / cm 2 , the total loading is 0.125mgPt / cm 2 From Table 3, it can be clearly seen that the N-co-doped fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF catalyst has higher catalytic activity than the single F-doped PtCuNiCoF / CF, where the rated power and peak power density achieved are 1.16 and 1.35 W / cm, respectively. 2 , higher than PtCuNiCo-F / CF (0.87, 1.01W / cm 2 The rated power and peak power density achieved by the PtCuNiCo-NF / C-NF catalyst are among the best in the industry.
[0154] Table 3 Fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF and PtCuNiCo-F / CF catalyst layers with hydrophobic microenvironment constructed in Examples 5 and 6 with a total loading of 0.125 mg Pt / cm 2 Rated power and peak power density under conditions of
[0155] catalyst Rated power (W cm) <![CDATA[Peak power density (W cm -2 )]]> PtCuNiCoF-1 / CF 0.87 1.01 PtCuNiCo-NF / C-NF 1.16 1.35
[0156] Comparative Example 2
[0157] The present invention found that in the synthesis process, the Pt precursor is crucial to the success of the synthesis of the F-doped quaternary platinum alloy. This comparative example is intended to verify the effect of adding a platinum precursor or not adding a platinum precursor in step 1 on whether the alloy can be synthesized.
[0158] The sample in this comparative example was prepared by the same steps as in Example 1, except that no platinum precursor was added in step 1, and other conditions were the same as in Example 1.
[0159] Fig.17This is the XRD spectrum of the sample prepared in Comparative Example 1. As can be seen from the figure, these diffraction peaks are mainly attributed to Cu single substance, indicating that when the Pt precursor is not added, the same synthesis method cannot prepare the alloy, and only Cu segregation occurs. This also tells us that the addition of the Pt precursor is crucial to the success of the synthesis process. The possible reason is that the Pt precursor is preferentially reduced to Pt, and the formation of the Pt nucleus first is conducive to the growth of the subsequent Pt alloy.
[0160] Comparative Example 3
[0161] In the present invention, we found that the subsequent high temperature heat treatment step is essential and plays a vital role in the activity and stability of the catalyst. In this comparative example, we tested and compared the electrochemical properties of the sample without high temperature heat treatment in step 3 and the sample with high temperature heat treatment.
[0162] The samples in this comparative example were prepared by the same steps as in Example 1, except that:
[0163] In step 3, high temperature heat treatment is not performed, and other conditions are the same as those in Example 1.
[0164] It is worth mentioning that the initial catalyst generated after the reaction in step 2 is already a fluorinated high-entropy platinum alloy catalyst with a hydrophobic microenvironment. Fig.18 As shown in the figure, the particle size of the catalyst is 5nm and is evenly dispersed on the carbon support. However, the subsequent high-temperature heat treatment helps H2 to further reduce the 3d transition metal, promote alloying, and allow more fluorine to enter the catalyst, thereby better optimizing the structure of the fluorinated high-entropy platinum alloy catalyst particles with a hydrophobic microenvironment and improving its catalytic activity and stability.
[0165] from Fig.19 From the LSV curve, it can be seen that the ORR activity of the sample subjected to high temperature heat treatment is much higher than that of the sample without high temperature heat treatment, and the half-wave potential is 0.952V and 0.883V respectively. The mass activity calculated at 0.9V (relative to RHE) also shows the same trend. The MA (2.56Amg pt -1 ) is the sample without high temperature heat treatment (0.36Amg pt -1 ) is 7.1 times.
[0166] Comparative Example 4
[0167] This comparative example is intended to demonstrate the comparison of the hydrophobicity of the N-element co-doped fluorinated high-entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer with a hydrophobic microenvironment constructed in Example 5, the fluorinated high-entropy platinum alloy PtCuNiCoF-1 / CF catalyst layer in Example 1, and the F-undoped PtCuNiCo / C catalyst layer in Example 2.
[0168] Fig. 20 This is the data graph of the contact angle experiment of PtCuNiCo / C, PtCuNiCoNF / C-NF and PtCuNiCoF-1 / CF catalyst layers. It can be seen from the figure that when water drops on PtCuNiCo / C, PtCuNiCoNF / C-NF and PtCuNiCoF-1 / CF catalyst layers, the contact angles are 31.55, 40.67 and 50.08° respectively, and the size of the contact angle gradually increases. This shows that the hydrophobicity of PtCuNiCo / C, PtCuNiCoNF / C-NF and PtCuNiCoF-1 / CF gradually increases, which further proves that the hydrophobicity of fluorinated high entropy platinum alloy catalysts can be regulated by doping with non-metallic elements.
[0169] Fig.21 The corresponding polarization separation diagram of the constructed PtCuNiCo-NF / C-NF and PtCuNiCo-F / CF catalyst layers with hydrophobic microenvironment under H2-AIR conditions. Fig.21 From the ohmic polarization curves of the three catalysts in Figure a, it can be seen that PtCuNiCo-NF / C-NF has the smallest ohmic polarization. Fig.21 b It can be seen that the activation polarization of PtCuNiCo-NF / C-NF and PtCuNiCo-F / CF is not much different, only slightly reduced. Fig.21 In c, the concentration polarization changes significantly with the change of catalyst, among which the concentration polarization of PtCuNiCoNF / C-NF is the smallest, especially in the high current region, where the reduction is greater. This shows that the N-co-doped fluorinated high-entropy platinum alloy PtCuNiCo-NF / C-NF not only has improved activity, but also further reduced mass transfer resistance compared to the single fluorine-doped PtCuNiCoF / CF catalyst. Therefore, in the N-co-doped fluorinated high-entropy platinum alloy PtCuNiCo-NF / C-NF, the doping of N is mainly to improve the activity, while the doping of F changes the hydrophobicity of the catalyst layer, which is conducive to the removal of water vapor and improves the transport of substances at the full cell level while maintaining H mass transfer.
[0170] Comparative Example 4
[0171] In order to further reflect the fluorinated high entropy platinum alloy with a hydrophobic microenvironment constructed in Example 1
[0172] The PtCuNiCo-NF / C-NF catalyst layer exhibits excellent electrochemical performance in fuel cells. We compared the electrochemical performance of the PtCuNiCo-NF / C-NF catalyst with the electrochemical performance of the platinum alloy catalyst in the full cell reported in the current top magazines. As shown in Table 4, the PtCuNiCo-NF / C-NF catalyst demonstrated in the present patent not only has high intrinsic activity and stability, but also can achieve high power density output of fuel cells at the membrane electrode level, which ranks first in the industry. Table 4 Comparison of the performance of the hydrophobic microenvironment fluorinated high entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer constructed by Example 5 of the present invention and the platinum-based catalyst published in the current top journals in H2-AIR fuel cells
[0173]
[0174]
[0175] In summary, the present invention provides a method for constructing a high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment, wherein the excellent electrochemical activity and stability of the fluorinated high-entropy platinum alloy PtCuNiCo-NF / C-NF catalyst layer with a hydrophobic microenvironment regulated by the N element in the fuel cell are mainly due to: (1) the doping of the N element is beneficial to improving the intrinsic activity and stability of the catalyst; (2) the doping of the highly electronegative F element is beneficial to reducing the electron density distribution of the catalyst layer, thereby facilitating the antioxidant and corrosion resistance of the catalyst particles and the carrier, while enhancing the hydrophobicity, facilitating the removal of water vapor, and improving mass transfer, thereby facilitating the improvement of stability; (3) by co-doping the two elements N and F and utilizing their synergistic effect, the constructed catalyst layer can not only maintain the high activity brought by the N element doping, but also further improve the stability by the F doping, so that at the full cell level, the fuel cell using the catalyst can show ultra-high activity and stability, and more importantly, can achieve the expression of ultra-high power density. The fluorinated high-entropy platinum alloy catalyst layer with a hydrophobic microenvironment constructed in the present invention can achieve the highest power density output in a fuel cell to date, and has very promising commercial application prospects. In addition, the design strategy of the catalyst layer has a great enlightening effect on the preparation of catalysts in the field of electrocatalysis.
[0176] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment, characterized in that: include, Fluorinated high entropy platinum alloy catalyst; A catalyst layer consisting of a fluorine-doped carbon support and a Nafion ionomer solution; wherein: The hydrophobicity of the catalyst layer can be further regulated by doping other light non-metallic elements (N, B) in the particles of the fluorinated high entropy platinum alloy catalyst and the fluorinated carbon support.
2. The fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment according to claim 1, characterized in that: The fluorinated high entropy platinum alloy catalyst in the catalyst layer includes at least PtCuNiCoF, PtCuNiCrF, PtCuNiFeF, PtCuNiCoNF, and PtCuNiCoNBF.
3. The fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment according to claim 1, characterized in that: The mass ratio of the Nafion ionomer solution is 4%-7%, and the mass ratio of the Nafion ionomer solution to the carbon carrier is 0.45-0.
8.
4. The method for constructing a fluorinated high entropy platinum alloy catalyst layer having a hydrophobic microenvironment according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: dissolving a certain amount of fluorinated high-entropy platinum alloy catalyst, fluorinated carbon carrier and Nafion ionomer in a mixed solvent of isopropanol and H2O; ultrasonicating in a water bath to obtain cathode catalyst ink; and spraying the uniform catalyst ink at a certain rate on one side of a proton exchange membrane by an ultrasonic sprayer to form a fluorinated high-entropy platinum alloy catalyst layer.
5. The method for constructing a fluorinated high entropy platinum alloy catalyst layer having a hydrophobic microenvironment according to claim 4, characterized in that: The preparation method of the fluorinated high entropy platinum alloy catalyst comprises the following steps: Step 1, after uniformly dispersing the platinum precursor, 3d transition metal precursor, structure directing agent, fluorine source or continuing to add other N, B non-metallic sources and solvent by ultrasonic dispersion, the carbon carrier is added and ultrasonic dispersion is continued to obtain a mixture; Step 2, heating the mixture in an oil bath while stirring, cooling to room temperature after the reaction is completed, centrifugally washing and vacuum drying to obtain an initial catalyst; Step 3, annealing the initial catalyst in a reducing atmosphere, and then cooling it to room temperature to obtain a stable catalyst; Step 4: centrifugally wash and dry the above-mentioned stable catalyst, and after acid treatment under an inert atmosphere, repeat the previous centrifugation washing and drying steps to obtain the final fluorinated high entropy platinum alloy catalyst.
6. The method for constructing a fluorinated high entropy platinum alloy catalyst layer having a hydrophobic microenvironment according to claim 5, characterized in that: In the step 1: The platinum precursor is one of acetylacetonate platinum, hexahydrate chloroplatinic acid, sodium chloroplatinate, and potassium chloroplatinate; The transition metal precursor is at least one of chloride, chlorate, nitrate, acetate and acetylacetonate of transition metal; The fluorine source is any one of perfluorobenzene, tetrafluoroterephthalic acid, PTFE, tetrafluoroterephthalonitrile, 2-fluoropyridine, ammonium fluoride, hexafluorobenzene, and PVDF; The nitrogen source is any one of ammonia water, ammonium nitrate, ammonium bicarbonate, ammonium chloride, urea, melamine, pipemidic acid, and 1,3-diamidazole; the boron source is any one of boric acid, phenylboric acid, sodium tetraborate, sodium borohydride, boric acid alcohol, and dimethylamine borane; The structure directing agent is any one of phenylacetic acid, benzoic acid, o-methylbenzoic acid, and acetic acid, and the directing agent also plays a certain reducing role; The solvent is any one of dimethylformamide, tetrahydrofuran and dimethyl sulfoxide, and the solvent also plays a reducing role; The molar ratio of the platinum precursor to each transition metal precursor, the reducing agent, the non-metal source and the carbon black is 0.5-1.5:1:40-55:8-11:30-40.
7. The method for constructing a fluorinated high entropy platinum alloy catalyst layer having a hydrophobic microenvironment according to claim 5, characterized in that: In the step 2: The reaction temperature is 160°C, the heating rate is 1-3°C / min, and the holding time is 8-16h; The solvent used for washing the mixture is at least one of deionized water, ethanol, acetone and cyclohexane, and the drying temperature is 40-100°C; In the step three: The annealing atmosphere is one of 10% H2 / Ar or N2, and the annealing temperature is 300-500°C; In step 4: The inert atmosphere is one of Ar or N2, the acid solution is one of nitric acid or sulfuric acid, the molar concentration is 0.1-1 mol / L, the acid treatment time is 8-10h, and the acid treatment temperature is 60-100°C.
8. The method for constructing a fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment according to claim 4, wherein the spraying temperature is 55-65° C. and the spraying distance is 9-11 cm 2 .
9. The fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment according to any one of claims 1 to 3 is used in fuel cell operation to significantly improve the performance in water management, oxygen mass transfer, activity, and stability.
10. Use of the fluorinated high entropy platinum alloy catalyst layer with a hydrophobic microenvironment according to any one of claims 1 to 3 in the oxygen reduction reaction (ORR) at the cathode of a fuel cell.